A ternary nanocomposite based on nickel(iii) oxide@f-CNF/rGO for efficient electrochemical detection of an antipsychotic drug (Klonopin) in biological samples. (5th June 2020) - Sriram, Balasubramanian; Govindasamy, Mani; Wang, Sea-Fue; Joseph, Xavier Benadict
Abstract : The formation of the Ni2 O3 @f-CNF/rGO composite for the electrochemical detection of KNP. Abstract : In this study, we developed a Ni2 O3 @f-CNF/rGO composite for the sensitive and selective electrochemical detection of Klonopin (KNP) via a simple ultrasonic method. Scanning electron microscope (SEM), high-resolution transmission electron microscopy (HR-TEM), energy-dispersive X-ray spectroscopy (EDS), X-ray powder diffraction (XRD), and Raman spectroscopy results demonstrated the successful formation of the Ni2 O3 @f-CNF/rGO composite. The electrochemical impedance spectroscopy (EIS) analysis of the Ni2 O3 @f-CNF/rGO-modified screen-printed carbon electrode (Ni2 O3 @f-CNF/rGO/SPCE) revealed a minimized charge transfer resistance ( R ct ) than those for Ni2 O3, f-CNF/rGO, and bare SPCE. In the electrochemical experiments, Ni2 O3 @f-CNF/rGO-modified SPCE exhibits superior performance towards the electrochemical detection of KNP, which provides an ultra-low detection limit of 2.8 nM in a wide concentration range of 0.08–1070.94 μM with a sensitivity of 12.02 μA μM −1 cm 2 using the amperometric i – t method. Moreover, the practical feasibility of Ni2 O3 @f-CNF/rGO was assessed for the electrochemical determination of KNP in the human blood serum and urine samples and the result indicated appreciable recovery of KNP.